Vaccine Hesitancy Among Sub-Sahara African Population: A Narrative Review and Empirical Case of South-South Nigeria - Onoriasakpobare Felix O."’, Igere Bright E."”, Chukuka Vivian I.'", Onianwah Ifeanyichukwu F." (Sokoto Journal of Medical Laboratory Science)
Vaccine hesitancy, a state of general rejection by individuals or refusal to be immunize, despite availability and clinically affirmed safety of vaccines has been associated with vaccine- preventable outbreaks and have hampered disease control and eradication programs such as polio eradication program in Nigeria. Such refusal of bio-control agents is not new as it has existed since the application of diverse vaccines (smallpox vaccine) and have notably increased in recent years. This study determined the level of vaccine hesitancy among Sub-Saharan population with emphasis on South-South region of Nigeria. The cross-sectional study employed a non-probability sampling method using questionnaire as the instrument for assessment of volunteers/informed consent participants (students in tertiary institutions, civil servants: teachers, traders and local farmers) across the states. The questionnaire was designed to reveal demographic information and information relating to the usage of 18 vaccines administered from childbirth to adulthood, while different communication tools were applied to ascertain clarity of questions, ease of form completion and language understanding for non-educated participants. It was observed that amongst the 800 respondents document received, 378 were observed to be eligible for analysis amongst which 272 (72%) were females and 106 (28%) were males. Amongst these, 250 (66%) were married and 128 (44%) were single. Also, 30 (8%) were uneducated, 37 (10%) had secondary education and 311 (82%) had tertiary education. Also, 33 (8.7%) were living in rural areas while 345 (91.3%) were living in urban areas. A total of 107 (28.3%) eligible participants’ responses demonstrated vaccine hesitancy despite high rate of vaccine availability (82.7%) and accessibility (90%) within the region. This is worrisome as it poses great risk for vaccine-preventable diseases outbreaks as well as viral infectious agents’ outbreaks. It is noteworthy to state that the effectiveness of vaccines is plausible only when it is acceptable and applicable. This was the reason why the World Health Organization (WHO) has identified vaccine hesitancy as one amongst 10 global health threats. The need for continuous awareness scheme on vaccine usage and usefulness (relevance) remains a germane strategy for vaccination and global health wellness.